Baas, Jordi Badia : Obitario municipale - García Vergara, Marisa (2003)
Artículo sobre la morgue municipal en Barcelona, España 2002.
Keywords: ARQUITECTURA; EDIFICIOS PUBLICOS; BAAS; BADIA, JORDI; ESPAÑA; BARCELONA; ARQUITECTURA FUNERARIA